1993
DOI: 10.1002/aja.1001970202
|View full text |Cite
|
Sign up to set email alerts
|

Development of the vasculature of the anterior pituitary: Ontogeny of basic fibroblast growth factor

Abstract: This study correlates the ontogeny of basic fibroblast growth factor (FGF) with the development of the vasculature of the anterior pituitary (AP) in two strains of rat, Sprague-Dawley (SD) and Fischer 344 (F344). Immunolocalization of FGF was followed from the first appearance of Rathke's pouch (RP) in 12-day (12d) fetuses, through each day of fetal development, and in 5,20, and 50d postnatal female rats. In addition, the ontogeny of folliculo-stellate cells (FSC) is described, since previous studies suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…However, bFGF was also demonstrated in the nuclei of parenchymal cells. Similar to our results in previous studies, bFGF was detected immunohistochemically in the nuclei of pituitary parenchymal cells in rats and humans [8,16]. In vitro studies [18,19] revealed that bFGF is first translated and located in the cytosol, and then translocates into and is accumulated in the nuclei.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, bFGF was also demonstrated in the nuclei of parenchymal cells. Similar to our results in previous studies, bFGF was detected immunohistochemically in the nuclei of pituitary parenchymal cells in rats and humans [8,16]. In vitro studies [18,19] revealed that bFGF is first translated and located in the cytosol, and then translocates into and is accumulated in the nuclei.…”
Section: Discussionsupporting
confidence: 80%
“…Several hypotheses have been proposed concerning the physiological roles of bFGF in the pituitary gland. In rat fetuses [8], immunopositivity for extracellular bFGF was observed at sites of capillary penetration adjacent to immature gonadotrophs during the early stages of pregnancy, and then bFGF was detected in the cytosol of a subpopulation of gonadotrophs. bFGF stimulates angiogenesis and plays an important role in tumorigenesis of prolactinomas in rats [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is no answer as to why some humans and animals are more responsive to estrogen's actions. However, it is interesting to note that there are slight structural differences in the pituitaries of estrogensensitive Fischer-344 and estrogen-insensitive Sprague-Dawley rats, including a difference in the number of supporting folliculo-stellate cells [30]. The differences in folliculo-stellate cell numbers between these two strains could be significant in tumorigenesis because these cells are a major source of bFGF, which regulates lactotropic cell proliferation [31].…”
Section: Estrogen-treated Ratsmentioning
confidence: 99%